Validity and reliability of a snatch pull test to model the force-velocity relationship in male elite weightlifters - Sandau, I.; Chaabene, H.; Granacher, U. (The Journal of Strength and Conditioning Research, 2022)
This study examined the concurrent validity and within-session reliability of parameters describing the force-velocity relationship (FvR) such as maximal force, velocity, power, and the theoretical one repetition maximum snatch performance (snatchth) during the snatch pull. The FvR was assessed using the multiple-load (FvRm) approach and the 2-load (FvR2) approach. Eight male elite weightlifters from the German national team executed the snatch pull in 2 separate experiments. For the concurrent validity assessment (experiment one), during the snatch pull, 7 loads from 70 to 100% were lifted to compute the FvRm, and 2 loads (70 and 100%) were lifted to compute the FvR2. For the reliability assessment (experiment 2), a test-retest protocol for the FvR2 was conducted. Input FvR parameters were determined from video-based barbell tracking. Results indicated no differences (all p > 0.05; all d = 0.07) and extremely large correlations (all r = 0.91) between the FvRm and FvR2 parameters. The within-session reliability of FvR2 parameters was excellent (all intraclass correlation coefficient =0.97; SEM% =1.23%). The percentage smallest real difference (SRD95%) of FvR2 parameters ranged between 1.89 and 3.39%. In summary, using the snatch pull to model FvR2 parameters is a valid and reliable approach that can easily be integrated into elite weightlifters' daily training routines.